The ANALISIS EFEKTIVITAS KINERJA MESIN GAS CUTTING OTOMATIS Di PT. ANEKA JASA TEKNIK GRESIK - zidan zakhroni; Alviani hesthi permata ningtyas (Universitas Muhammadiyah Gresik, 2025)
The effectiveness of cutting machines plays a crucial role in improving productivity within manufacturing industries, particularly in steel plate cutting processes. This study aims to analyze the performance effectiveness of the HK-12 Automatic Gas Cutting Machine at PT Aneka Jasa Teknik Gresik using the Overall Equipment Effectiveness (OEE) method. The analysis focuses on three key parameters: Availability, Performance, and Quality, based on operational data collected during the internship period. The results indicate that the machine achieved an Availability value of 95.83%, demonstrating a high level of operational readiness with minimal downtime. However, the Performance value reached only 14.13%, showing that the cutting speed is significantly below the ideal operating speed. The Quality value was recorded at 86.67%, meaning that most cutting outputs met the required standards although some defects were still present. Based on these three components, the overall OEE value was calculated at just 11.73%, far below the industrial OEE benchmark of 85%. The low OEE result is primarily attributed to poor machine performance, influenced by suboptimal cutting speed, track conditions, and operator parameter settings. Overall, improvements in machine performance, regular maintenance, and operator training are needed to enhance the effectiveness of the HK-12 Automatic Gas Cutting Machine.